2022
DOI: 10.1039/d2nr01800d
|View full text |Cite
|
Sign up to set email alerts
|

A GO/CoMo3S13 chalcogel heterostructure with rich catalytic Mo–S–Co bridge sites for the hydrogen evolution reaction

Abstract: This article proposes an efficient GO/CoMo3S13 chalcogel heterostructure catalyst for the hydrogen evolution reaction through the synergetic combination of the active Mo–S–Co bridge sites with shortened charge transport on graphene oxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Heterogeneous catalyst components possess distinct energy levels and morphological structures, 111,112 which can expose more active sites or increase the activity of the original active site, 113 and enhance mass transfer efficiency. To effectively reduce the initial potential and charge transfer resistance, while meeting the requirements of HER processes, considerable research has been dedicated to construct heterogeneous catalysts with various heterogeneous interfaces.…”
Section: Composite Catalystsmentioning
confidence: 99%
“…Heterogeneous catalyst components possess distinct energy levels and morphological structures, 111,112 which can expose more active sites or increase the activity of the original active site, 113 and enhance mass transfer efficiency. To effectively reduce the initial potential and charge transfer resistance, while meeting the requirements of HER processes, considerable research has been dedicated to construct heterogeneous catalysts with various heterogeneous interfaces.…”
Section: Composite Catalystsmentioning
confidence: 99%
“…The distinctive features of transition‐metal sulfide (TMS x ) chalcogel materials, including large porosity, extensive surface area, and exceptional electrochemical properties, have recently captured the attention of researchers in the field of catalysis. Several noteworthy studies have reported significant improvements in the catalytic performance and stability using TMS x chalcogels such as 40% GO/CoMo 3 S 13 , CoMoS x , and CoMoS x /nickel foam (NF) chalcogels 93,284,285 . Moreover, recent research has focused on understanding the gas–liquid–solid three‐phase interfaces in CoMoS x chalcogels on NF, which suggest that TMS x chalcogels can be promising materials for electrochemical catalysts 285 …”
Section: Metal‐chalcogenide–derived Aerogel (Chalcogel)mentioning
confidence: 99%
“…(G) HER polarization curves before and after the stress test of 2000 cycles for 40% GO/CoMo 3 S 13 chalcogels. Reproduced with permission: Copyright 2022, The Royal Society of Chemistry 93 …”
Section: Metal‐chalcogenide–derived Aerogel (Chalcogel)mentioning
confidence: 99%
See 1 more Smart Citation
“…1–3 The hydrogen evolution reaction (HER) in alkaline media offers tremendous potential for industrial hydrogen production; alkaline electrolytes can be generated from available and affordable materials. 4 Pt-Based materials are utilized as catalysts in the commercial HER process; however, their applicability is limited by their high cost and activity degradation. Therefore, the production of inexpensive Pt-free electrocatalysts with improved performance and stability is desirable.…”
Section: Introductionmentioning
confidence: 99%